Tinta Emosi: Petualangan Puisi Saat Galau Yang Menginspirasi - Henny Futry Ananti; Jumadi Jumadi; Dwi Wahyu Candra Dewi (Universitas Palangka Raya, 2024)
Poetry is an art form that allows writers to express troubled feelings with beautiful and deep words. This journal, “Emotional Ink: An Inspiring Poetry Adventure When You're Upset,” explores the relationship between anxiety and creativity in poetry. In the introduction, this journal introduces the importance of poetry as a unique medium of expression and provides an overview of the research aims. The research method uses a literature review to gain in-depth insight into leadership and team productivity. The results and discussion explain the role of poetry as a means of emotional expression and psychological therapy, while the conclusions highlight the power of poetry as a healing tool during difficult times.